Urban Agriculture: The Allotment Gardens as Structures of Urban Sustainability - Sousa, Rute (2014)
This reflexion comes from a look over the city, particularly the relationship between the built and the open spaces that constitute it. In this look we came across the enormous importance that the system of open spaces has and has always had on the construction of the city, its balance, its identity and its experience. On a closer approach to the system of open spaces of the city, we were confronted with the existence of typologically qualified spaces and of spaces without any typological attribution but that are, by no means, less important than the former. Open spaces, interstices between the built fabric of the contemporary city, that present a certain continuity and that allow the flow of air, of water and matter, simultaneously with the flow of residents or casual users. Sometimes, besides that flow, an informal appropriation of these spaces as spaces for fun, games and socializing is verified, emphasizing the enormous potential presented in the structure and cohesion of the city as support of the urban experience, of social interaction and, of the development of the sense of community. About these spaces, several questions have been raised concerning its quality and diversity, namely its lack of integration in a recognized urban typology and all the consequences that this determines. However, we considered that this fact, on its own, does not constitute a negative factor, but a distinct reality determined by the ever-accelerating rhythm of the technological, economical, social, cultural and demographic chances. The need to understand the presence of these spaces leads us to a study and analysis of the evolution of the city and of the transformation process that has been occurring, not only in the conceptual and ideological point of view, but also in morphological terms determined by different social-economical and cultural contexts. During this project we verified that the characteristic discontinuity of the suburbs was the result of an urban model that, since the 60's of the 20th century, has given birth to a new concept of city and, in a disorderly growing process, allowed a landscape of problematic suburbs to arise, anarchically, in an unqualified territory. The interstices over which we lean are the consequence of this extensive growth of cities and its suburbs. Aware of the existence of these unnamed intervals, in the city, the open space continues, frequently, to be called green and to, still, play a secondary role on the construction of the urban landscape. Despite its high potential in the structure and cohesion of the city, these spaces – the interstices and the greens – and the attitude of indifference that has been verified towards its qualitative definition tends to reduce them to nothing more than another index in the city's statistics. Thus, it is necessary a new understanding on the urban condition of the interstitial spaces and on the importance of the quality of the landscape. We consider fundamental to implement an intentional and adequate use of these spaces, as a vital condition to its defense, in a positive way, guaranteed by its comprehension and enjoyment, recognizing them as the true potential to the development and experience of the city. They should, then, be acknowledged as spaces of urban cohesion, fundamental and complementary to the built space and its articulation with the surrounding, ecologically, aesthetically, culturally, socially, economically and technologically. With the purpose of obtaining a bigger understanding on the quality of the landscape, and based on the idea that this should appear as a fundamental structure and a cornerstone on the qualification of the city, we leaned on its inherent multifunctionality From here starts the conscious notion that the landscape is a recent conquest in the western culture, being considered as such from the moment Man inscribes it in a determined culture and epoch. Intrinsic to the concept of landscape come the concept of multifunctionality to which the concepts and the practices of production, leisure and protection have always been associated. However, this dimension and multifunctional look are lost with the modern movement where, the sectoral zoning does not allow the coexistence of several roles thus appearing the vague concept of green space, that stretches throughout the entire city homogeneously, amorphous and residually. It becomes, then, urgent and primordial the return to that concept of landscape. Several authors, searching for new strategies that lead to the multifunctionality of the landscape and its understanding, defend that in the open spaces of the city it should be implanted a continuous and structuring fabric where landscape would appear as a fundamental structure of this continuum, having as a principle the systemic vision of the landscape, long implicit in practice and in the philosophy of landscape architecture, from the continuous system of public parks designed by Olmsted, to the concept of continuum naturale, introduced and developed, in Portugal, by Professor Caldeira Cabral, in the middle of the last century, covering all the projects that include the concepts of green corridors and of green or ecological structures, all of them essential, since they allow the occurrence of ecological processes, fundamental to the growth and sustainable development of the city. As well in the recent current, designated as Landscape Urbanism (1996), that appears with the rekindle of environmental and ecological concerns, such as the growth of tourism and the questions connected with it, with the sense of oneness and entity, as well as with the impact that the massive growth of cities has over the rural space, the landscape is proposed as model to the urbanism, and it is recommended the integration of public landscapes with the infra-structural systems, formalizing and leading the urban development, similarly to what happened with Central Park in New York and the continuous system of the Boston Parks by Frederick Olmsted, where the landscape lead the process of the formation of the city. In this search for the lost multifunctionality it is frequent the reference to the aesthetic, social, ecological, economical and cultural components and consequently, the role of protection, production and leisure. It then begins to take shape, in this study, the idea of production associated with leisure as a fundamental component of landscape that structures, qualifies, and gives continuity to the urban fabric through its interstitial spaces, open spaces and suburbs, all the way to the countryside, promoting an articulated relationship between this old city-countryside dichotomy. Our main purpose is the proposal of a new project approach that provides the creation of a multifunctional structure of landscape dedicated to production and leisure in an urban context. In this perspective, the interstitial spaces, object of this study, can and should be a current expression of the landscape continuum, given that it allows the occurrence of the ecological processes and of the fundamental biological cycles to the harmonious and balanced development of the city. This desideratum is accomplished, or can consubstantiate itself, through urban agriculture, which is perfectly compatible with recreational and leisure activities, as has been long advocated by Ribeiro Telles, and it is even proposed in his “Plano Verde de Lisboa” - Lisbon's Green Plan [1]-, and how it has been proved by the “quintas de recreio” (recreational farms), in Portugal. Although urban agriculture refers, in general, to activities connected to the production of fresh vegetables in the city, it does not mean that it has to be strictly related with production; urban agriculture is also fundamental on including ecological, cultural, recreational and aesthetic concerns, related to the landscape. This means, urban agriculture can integrate, and be, a structuring continuum that assures the occurrence of the processes and flows of the various systems that constitute the landscape. This structure should be ecologically justified, as well as it should be developed according to the holistic view that the landscape demands in and for its understanding. In it, there should be present the ecological, aesthetic, social, economical and cultural components and from it there should result spaces and economical, social, cultural, aesthetic and ecologically balanced structures. Urban agriculture can be based in the ecological principles of life and on the necessary space to process its actions, reactions and interactions. It can be considered, even, as other elements of the urban infra-structure: wide and complex, and demanding planning and design, management and maintenance. This means, it is perfectly compatible with the holistic concerns of landscape architecture. In this sense, urban architecture is considered, in this study, in its several dimensions – ecological, cultural, social, economical and aesthetic – as a constituent of the natural and cultural continuous that structures the urban and suburban fabric, through its open spaces and interstices, making the articulation and establishing an inter-relationship with the countryside. We consider that this option is based on three pillars: one with a historical and temporal character – the multifunctionality (promiscuity) of the Mediterranean landscape, from which the meridional Portuguese landscape is a part; another of a conceptual and practical character, that concerns the theory and the praxis of landscape architecture and of the landscape urbanism; and lastly, in our own opinion, the answer that may be given by the urban architecture to the global crisis situation and of the growth of the estimated urban population (already felt) in the next decades, which lead us to approach the theme of urban agriculture in a more general way. According to Food and Agriculture Organization (FAO) (2009), for the first time in the history of humanity, there is a bigger concentration of population in the cities than in the countryside. This urbanization process determines big challenges to the planning, management, maintenance and conservation of the urban areas. In the beginning of the third millennium we inhabit a world with an unprecedented number of population. There are currently around 6.3 billion people, a number that it is expected to rise to 9 billion, in 2050 (FAO, 2009). Around half of the world population lives in cities, and this estimation is expected to rise to two thirds by 2030. A great number of cities grow over agricultural terrains, a fact that certainly reduces the capability to produce a considerable amount of the food necessary to the auto-sustainability of the city. It is estimated that if the developing countries follow the western lifestyle – in terms of the usage of food, forest and energy products – three whole planets will be needed. It is, then, of crucial matter that the city becomes much more efficient in the way it utilizes its resources, which includes, obviously, the production of food. Urban agriculture constitutes, in this case, a fundamental contribution to the auto-sustainability of the city. Moreover, urban agriculture will be a practice that won't compromise uses or future options, thus becoming a guaranty of soil preservation, a scarce and fundamental resource. The following chapter is centered on the theme of urban agriculture, namely its definition, identification and characterization, emphasizing three of its typologies based on relevance and inclusion in the objectives of this study. They are: the urban allotment garden, the continuous productive landscapes and the urban field. In this context, we leaned over its relevance and the need in the contemporary city when facing the current social-economical crisis and the estimated urban growth in a near future. The benefits that can be brought and the obstacles that can occur are presented, either at a food and nutritional safety level, either at a health and local development level, or even at a social-cultural and urban environmental management level. The politics that regulate urban agriculture in its social, economical and ecological dimensions are addressed, and how it has influenced its practice, as well as the economical issues associated. We considered fundamental the study of agriculture throughout history and its evolution in the city, its relationship with the countryside, as well as the possibility of its integration in the interstitial urban spaces and, consequently the relevance of its contextualization, in the landscape urbanism, something that it is not the happening today. Lastly, we concluded with the proposal of integrating urban agriculture in a new approach to the landscape design in an urban context, but also in conceptual terms. And, with the presentation of strategies to the development of a sustainable urban agriculture, in order to contribute to a return to the multifunctionality of the landscape, which promotes the existence of a structure of continuous landscape where the recreation, the production and protection should be present and inseparable, thus contributing to urban sustainability.